The Relationship between Saccadic Choice and Reaction Times with Manipulations of Target Value - Milstein, David M.; Dorris, Michael C. (Frontiers in Neuroscience, 2011)
Choosing the option with the highest expected value [reward probability x reward magnitude] maximizes the intake of reward under conditions of uncertainty. However, human economic choices indicate that our value calculation has a subjective component whereby probability and reward are not linearly weighted. Using a similar economic framework our goal was to characterize how subjective value influences the generation of simple motor actions. Specifically, we hypothesized that attributes of saccadic eye movements could provide insight into how rhesus monkeys, a well-studied animal model in cognitive neuroscience, subjectively value potential visual targets. In the first experiment, monkeys were free to choose by directing a saccade towards one of two simultaneously displayed targets, each of which had an uncertain outcome. When faced with outcome uncertainty, choices were more likely to be allocated towards the higher valued target. In the second experiment, only one of the two possible targets appeared on each trial. When faced with this movement uncertainty, saccadic reaction times (SRTs) decreased towards the higher valued target. Across expected values blocks, a strong relationship was observed between choice preferences and SRTs in these two conditions. This relationship suggests that SRTs provide an index of expected subjective value. Lastly, SRTs were unchanged when all rewards were 1x, 1.5x and 2x their normal magnitudes, indicating that saccade preparation was influenced by the relative value of the targets rather than the absolute value of any single target. We conclude that value is not only an important factor for deliberative decision making in primates, but also for the selection and preparation of simple motor actions, such as saccadic eye movements. More precisely, our results indicate that, under conditions of uncertainty, saccade generation is influenced by the relative expected subjective value of potential movements.